POLA MANAJEMEN PERPUSTAKAAN BERBASIS INKLUSI SOSIAL DI DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH KABUPATEN SUMBAWA BARAT - Ahmad Muslim; Masita; Rudi Hariawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
This study aims to describe the pattern of social inclusion-based library management in the Regional Library and Archives Service of West Sumbawa Regency. The focus of this research are 1) How to socialize and promote social inclusion-based library strategies, 2) How to manage social inclusion-based libraries, 3) How to provide social inclusion-based library services. The research method uses a qualitative approach with a case study design. The location of this research was carried out at the Regional Library and Archives Service of West Sumbawa Regency which was located in the Kemutar Telu Center (KTC) Environment, Kuang Village, Taliwang District, West Sumbawa Regency with the technique of determining the subject of pourposive snowball sampling with a total of 13 informants. Data collection techniques using observation, in-depth interviews, and documentation. Data analysis used single case data analysis with interactive model from Miles & Huberman. The results of the study conclude 1) To increase the interest of library visitors, collaborate with various parties and carry out promotions and socialization through social media such as Facebook and Instagram. 2) Management in this library still follows the standard. 3) This library provides services such as on-site reading services, mobile library services, cross-service services, free library membership card making services, free wifi services, toilet services for the disabled, and braille Qur'an services for visitors with special needs. With this service, it is hoped that it will attract visitors to visit the library. The suggestion is that the community is expected to continue to optimize the implementation of social inclusion-based libraries.